Cultivating change: the long-term impact of forced labour in Mozambique - Margherita Bove; Rute Martins Caeiro; Rachel Coelho; Sam Jones; Patricia Justino (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Following the abolition of slavery, various forms of compulsory labour were adopted by colonial powers to develop their economies. This paper analyses the contemporary consequences of compulsory cotton production-a forced labour system that operated in colonial Mozambique from 1926 to 1961. During this period, the Portuguese colonial government granted geographic concessions to private companies, within which smallholder farmers were forced to cultivate cotton for payment in cash. Women bore the brunt of this regime, but in doing so often took on responsibilities traditionally reserved for men and engaged in active resistance strategies. Employing a spatial regression discontinuity, we explore the enduring impact of this exposure to forced cotton cultivation on present-day human and social capital, focusing specifically on rural southern Mozambique. Our estimation strategy relies on the arbitrarily defined historical borders of the concessions, which reflected the tendency of concessionaires to absorb as much territory as possible, often ignoring agronomic conditions. Drawing on bespoke individual-level survey data collected along the concession border, we find lower educational outcomes among women in former concession areas. However, this is counterbalanced by positive effects on social capital, in the form of higher levels of civil participation, more progressive attitudes towards gender norms, and an increased presence of women in leadership positions. These results suggest that exogenous ruptures that push women outside traditional boundaries can help to reinforce their role in society.
Keywords: F54; I24; J16; D02; 330; long-run development; violence; gender; social capital; regression discontinuity